PPF Dependent Fixed Point Results for Triangular αc-Admissible Mappings - Ljubomir Ćirić; Saud M. Alsulami; Peyman Salimi; Pasquale Vetro (The Scientific World Journal)
We introduce the concept of triangular αc-admissible mappings (pair of mappings) with respect to ηc nonself-mappings and establish the existence of PPF dependent fixed (coincidence) point theorems for contraction mappings involving triangular αc-admissible mappings (pair of mappings) with respect to ηc nonself-mappings in Razumikhin class. Several interesting consequences of our theorems are also given.